2016
DOI: 10.1097/md.0000000000002410
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine for Improving Quality of Life Among Nonsmall Cell Lung Cancer Patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Even after clinical treatment, five-year survival rate is still low [ 23 25 ]. Current clinical evidence has indicated that in comparison to patients with non-small cell lung cancer (NSCLC) receiving chemotherapy, the patients using traditional Chinese medicine (TCM) had longer lifespan and higher quality of life [ 26 ]. Thus, the component formula with definite and effective components provided new opportunity to treatment lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Even after clinical treatment, five-year survival rate is still low [ 23 25 ]. Current clinical evidence has indicated that in comparison to patients with non-small cell lung cancer (NSCLC) receiving chemotherapy, the patients using traditional Chinese medicine (TCM) had longer lifespan and higher quality of life [ 26 ]. Thus, the component formula with definite and effective components provided new opportunity to treatment lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse effects include cardiotoxicity, nephrotoxicity, hepatotoxicity, and peripheral neuropathy (Duwe et al, ; Ma, Kavelaars, Dougherty, & Heijnen, ; Santoni et al, ; Sharbaf et al, ). Sometimes, the adverse effects severely affect the daily quality of life for patients (X. Wu et al, ). Many of the adverse effect of chemotherapeutic drugs are caused by the drug itself and its metabolites, usually by inducing ROS formation (Varricchi et al, ).…”
Section: Herbal Compounds With the Potential To Synergize With Antitumentioning
confidence: 99%
“…In addition, previous studies confirmed that CKI had the effect of heat-clearing, dampness-expelling, blood cooling, detoxification, and sanjie analgesic effect [ 20 ]. It is extensively used for the treatment of pain and bleeding with malignant tumor such as liver cancer [ 21 ], lung cancer [ 22 ], and gastrointestinal cancer [ 18 ]. The suggested mechanisms of action are increasing protein expression, inhibiting vascular endothelial growth factor expression in neoplastic tissues, killing cell activity, inducing tumor cells to normal cell differentiation, and promoting cell apoptosis and so on [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%